Hybrid substrate for high frequency, millimeter wave radar, and antenna

By using a resin composition of the vagosiosyl sulfurlin resin and a specific thermoplastic resin as the layer of the low -agent electric material, the problem of the existing high -frequency mixed substrate conductivity and the uneven material of the material are solved. Herojinity has significantly improved high -frequency transmission performance.

CN119383831APending Publication Date: 2025-01-28DIC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410433399.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-04-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing high-frequency hybrid substrates have problems of reduced conductivity and material unevenness when using low dielectric materials, which is difficult to meet the needs of high-frequency transmission.

Method used

Volidal compositions containing vagosal sulfur sulfur resin and specific thermoplastic resins are used as low -agent material layers. By dispersed and continuous combinations, the dense and reflux of the metal layer and epoxy glass layer is improved sex.

Benefits of technology

The high -frequency mixed substrates with low -agency electricity loss, flame retardant, low water absorption and high -density connectivity have significantly improved transmission performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119383831A_ABST
    Figure CN119383831A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a high-frequency hybrid substrate, a millimeter-wave radar, and an antenna that have excellent reflow resistance and adhesion to a metal layer or an epoxy glass cloth laminate by using a printed wiring board comprising a polyarylene sulfide resin film in which a specific thermoplastic resin is dispersed. It is found that the problem can be solved by using a high-frequency hybrid substrate, thereby completing the present invention. A high-frequency hybrid substrate obtained by laminating, on one or both surfaces of a printed wiring board comprising an epoxy glass cloth laminate and a metal layer, (A) a polyarylene sulfide resin containing as a main component and (B) a thermoplastic resin other than a polyarylene sulfide resin having a glass transition temperature of 200 DEG C or higher or a melting point of 230 DEG C or higher The resin layer of the resin composition is formed as a printed wiring board of a low dielectric material layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-frequency hybrid substrate, a millimeter wave radar and an antenna. The high-frequency hybrid substrate comprises a printed wiring board (2) having a low dielectric material as an insulating layer laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate. Background Art

[0002] In the fields of high-speed and large-capacity communications (5G) or vehicle-mounted millimeter-wave radar, a high-frequency substrate formed of a low-dielectric material and metal wiring is required, which has low transmission loss even when using high frequencies. However, low-dielectric materials are expensive, so the following high-frequency hybrid substrate has been developed, in which low-dielectric materials are used only in the antenna part or high-frequency transmission part of the surface layer, and a printed wiring board (1) formed of an insulating layer formed of an epoxy glass cloth laminate, which is a relatively cheap general material, is used for low-frequency wiring for control or power supply. In addition, in the high-frequency hybrid substrate, the high-frequency wiring layer of the printed wiring board (2) on the surface layer is formed by a multilayer of more than three layers, thereby predicting an increase in the use of higher functionality.

[0003] As a technology for high-frequency hybrid substrates, for example, reference 1 can be cited. This has the following advantages: printed wiring boards (1) and (2) can be connected using solder or conductive paste and can be manufactured with good productivity, but in this case, it also has the following disadvantages: the conductivity is reduced compared to the conduction using metal foil or plating layer. In addition, a low dielectric material with a glass cloth base material is used as a high-frequency substrate, so the problem is that the material inhomogeneity caused by the glass cloth in the low dielectric layer occurs.

[0004] The following method is proposed in reference 2: in a multilayer printed wiring board having an asymmetric structure of a printed wiring board (1) including a common insulating layer and a printed wiring board (2) using a low dielectric material as an insulating layer, a high-frequency substrate is laminated using an adhesive layer on a single side of a printed wiring board formed of an insulating layer formed of an epoxy glass cloth laminate as a core layer, and a resin layer formed by the same adhesive layer is formed separately on the opposite side, thereby manufacturing a multilayer printed wiring board with excellent low warpage. However, in order to suppress warpage, it is necessary to add a resin layer formed by an adhesive layer, so there is a problem of reduced design freedom or complicated process. In reference 3, a high-frequency hybrid substrate with excellent drilling processability is obtained by using a printed wiring board (1) for a core layer, but a low dielectric material with a glass cloth substrate is used for the printed wiring board (2) using a low dielectric material as an insulating layer, so there is a problem of material non-uniformity within the surface.

[0005] The printed wiring board (2) on the surface layer comprises a low dielectric material and metal wiring (conductive material). As the low dielectric material, a low dielectric material of a glass cloth substrate is sometimes used as described above. However, in the case described above, the non-uniformity of the insulating material caused by the mesh of the glass cloth becomes a factor of deviation of the electrical properties, or the presence of the mesh of the glass cloth easily induces concavo-convex on the surface of the insulating material, so it is required to use a low dielectric material without using glass cloth.

[0006] In order to form a printed wiring board (2) formed of a low dielectric material without glass cloth on the surface layer of the printed wiring board (1), there is a method of applying a solution of the low dielectric material and then drying and hardening it to form a low dielectric material layer. However, there is the problem of trouble caused by the drying process of the solvent, or the problem of deterioration of the smoothness of the surface during the drying process. Therefore, in the method of attaching a film of the low dielectric material (hereinafter referred to as the low dielectric film) to the printed wiring board (1), the process is simple and it is easy to obtain a smooth surface, so it is preferred.

[0007] As raw materials for low dielectric films, fluorine-based resins, liquid crystal polymers (hereinafter, sometimes referred to as "LCP"), cyclic olefins (hereinafter, sometimes referred to as "COP (cyclo olefin polymer)"), modified polyimides (hereinafter, sometimes referred to as "MPI"), polyarylene sulfide (PPS (polyphenylene sulfide))-based resins (hereinafter, sometimes referred to as "PAS-based resins"), etc. are known. Among them, the dielectric properties of fluorine-based resins are very excellent, but they are expensive or have poor adhesion, so there is a problem that lamination or copper wiring is not easy to adhere. The dielectric properties of LCP are also excellent, but they are expensive or easily peeled off in layers, so there is a problem that it is difficult to laminate printed wiring boards (2). In addition, the adhesion and heat resistance of COP are also poor. MPI is easy to absorb moisture, so there is a problem of poor dielectric properties under high humidity.

[0008] Low dielectric films using polyarylene sulfide resin (PAS) also have good dielectric properties, excellent heat resistance, flame retardancy, and low moisture absorption, and are therefore suitable as low dielectric materials for high-frequency hybrid substrates. However, there are problems such as insufficient adhesion to low-sparseness copper foil and insufficient reflow resistance.

[0009] [Prior art literature]

[0010] [Patent Document]

[0011] [Patent Document 1] Japanese Patent Application Publication No. 2020-174115

[0012] [Patent Document 2] Japanese Patent Application Publication No. 2016-40797

[0013] [Patent Document 3] Japanese Patent Application Laid-Open No. 6-5998 Summary of the invention

[0014] [Problems to be solved by the invention]

[0015] The present invention provides a hybrid substrate for high frequency use, characterized in that a printed wiring board using a film containing a polyarylene sulfide resin in which a specific thermoplastic resin is dispersed (hereinafter, sometimes referred to as a PAS film) as an insulating layer is used, and the printed wiring board has excellent close contact with the insulating layer formed by an epoxy glass cloth laminate and excellent reflow resistance.

[0016] [Technical means to solve the problem]

[0017] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by using a high-frequency hybrid substrate, which is a printed wiring board (2) having an insulating layer formed of an epoxy glass cloth laminate and a resin layer comprising a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher, laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate as a low dielectric material layer.

[0018] That is, the present invention relates to the following (1) to (10).

[0019] (1) A high-frequency hybrid substrate, comprising a printed wiring board (2) having an insulating layer made of a low dielectric material and laminated on one or both sides of a printed wiring board (1) having an insulating layer made of an epoxy glass cloth laminate, wherein:

[0020] The low dielectric material includes a resin composition of a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher.

[0021] (2) The high-frequency hybrid substrate according to (1), wherein the ratio of the blending amount of the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher relative to the total amount of 100% by mass of the polyarylene sulfide resin (A) and the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is in the range of 3% by mass to 49% by mass.

[0022] (3) The high-frequency hybrid substrate according to (1) or (2), wherein the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is a dispersed phase having an average dispersed diameter of 5 μm or less.

[0023] (4) A high-frequency hybrid substrate according to any one of (1) to (3), wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is at least one selected from polyphenylene ether resin, polyether sulfone resin, polyphenylsulfone resin, polyetherimide resin, polysulfone resin, and fluorine-based resin.

[0024] (5) The high-frequency hybrid substrate according to any one of (1) to (4), wherein the low-dielectric material has a dielectric constant of 3.4 or less.

[0025] (6) The high-frequency hybrid substrate according to any one of (1) to (5), further comprising a modified elastomer (C) obtained by imparting a reactive group to the resin composition of the low dielectric material.

[0026] (7) The high-frequency hybrid substrate according to (6), wherein the modified elastomer (C) comprises an olefin-based polymer having at least a functional group selected from an epoxy group and an acid anhydride group.

[0027] (8) The high-frequency hybrid substrate according to (6) or (7), wherein the modified elastomer (C) is blended in an amount of 1% to 15% by mass relative to 100% by mass of the total of the polyarylene sulfide resin (A), the thermoplastic resin (B), and the modified elastomer (C).

[0028] (9) The high-frequency hybrid substrate according to any one of (6) to (8), wherein the α-olefin content of the modified elastomer (C) is 50% by mass to 95% by mass based on the total mass of the modified elastomer.

[0029] (10) The high-frequency hybrid substrate according to any one of (6) to (9), further comprising 0.01% by mass to 5% by mass of a silane coupling agent (D) having at least one functional group selected from an epoxy group, an amino group, and an isocyanate group.

[0030] (11) A millimeter wave radar and an antenna using the high frequency hybrid substrate according to any one of (1) to (10).

[0031] [Effects of the Invention]

[0032] According to the present invention, a high-frequency hybrid substrate having low dielectric loss tangent or flame retardancy in the surface layer low dielectric material, low water absorption, high adhesion to the metal layer, high adhesion to the epoxy glass cloth layer, and excellent reflow resistance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low dielectric material is laminated on one side of a printed wiring board (1) having an insulating layer made of an epoxy glass cloth laminate.

[0034] Figure 2 The present invention is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low dielectric material is laminated on both surfaces of a printed wiring board (1) having an insulating layer made of an epoxy glass cloth laminate. DETAILED DESCRIPTION

[0035] Hereinafter, the embodiment for carrying out the present invention will be described in detail.

[0036] Figure 1 The present invention is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low dielectric material is laminated on one side of a printed wiring board (1) having an insulating layer made of an epoxy glass cloth laminate. Figure 2 The present invention is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low dielectric material is laminated on both surfaces of a printed wiring board (1) having an insulating layer made of an epoxy glass cloth laminate.

[0037] [Printed wiring board (1) including an insulating layer formed of epoxy glass cloth laminate]

[0038] The epoxy glass cloth laminate used in the present invention is a plate-shaped insulating material obtained by impregnating glass cloth with epoxy resin and semi-hardening it, that is, a composite material, that is, a prepreg, alone or stacked to a desired thickness, and then subjected to a heat curing treatment. It is a material widely used for its flame retardancy and low conductivity, but it is an insulating material with insufficient low conductivity when used in high-frequency applications such as 5G communications or millimeter wave antennas. As a method for manufacturing a printed wiring board (1) using the insulating material, a known method can be used. For example, after attaching copper foil to one or both sides while heat curing, a wiring pattern is formed by a resist etching method, and then wiring is formed in the thickness direction by perforating with drilling or laser, and by imparting conductivity by through-hole plating to the holes, thereby obtaining a single-sided or double-sided printed wiring board (1). Furthermore, a prepreg of a semi-hardened composite material of glass cloth impregnated with epoxy resin is used as an adhesive layer, and the single-sided or double-sided printed wiring board (1) is multilayered by heat treatment, thereby obtaining the printed wiring board (1) used in the present invention. In addition, the wiring in the thickness direction can also be formed by forming through holes by drilling after manufacturing the multilayered printed wiring board (1), and then connecting the through holes by plating or conductive resin. As an insulating material for the printed wiring board (1), the epoxy glass cloth laminate is a general material that takes into account both flame retardancy and low conductivity, and has good electrical insulation stability or flatness, so it is most suitable. Among them, in order to reduce costs, a printed wiring board formed by a glass composite substrate, a paper epoxy substrate, a paper phenol substrate, etc. can also be used.

[0039] [Printed wiring board using low dielectric material as insulating layer (2)]

[0040] Regarding the manufacturing method of the copper-clad low-dielectric material used in the present invention, copper can be coated on the low-dielectric material alone, or the printed wiring board (1) can be coated with copper on the outermost layer after the low-dielectric material is attached or at the same time. As a method for copper coating the low-dielectric material, it can be hot lamination, or it can be attached using an adhesive or a bonding sheet, and a metal layer can be formed using a plating method such as a sputtering plating method. In the case of attaching copper foil, in order to reduce the transmission loss at high frequencies, it is preferred that the surface of the copper foil is smooth. For example, Rz is preferably less than 3μm, but a copper foil with suitable bumps can be selected according to the application. The processing cost in the plating method is higher than that of attaching copper foil, but it has the advantage of smoothing the interface between the insulating layer and the metal layer, so it is suitable for situations where it is required to reduce the transmission loss at high frequencies.

[0041] By forming a wiring pattern on a copper-clad low dielectric material using a known method, a printed wiring board (2) using the low dielectric material as an insulating layer can be obtained. The wiring forming method is not particularly limited, and examples thereof include: a method of forming wiring on the copper-clad low dielectric material by etching, a method of directly forming a metal layer at a necessary position of the low dielectric material, a method of combining the two, and the wiring formation can be performed by a subtractive method, a semi-additive method, a full-additive method, etc.

[0042] [Resin composition of low dielectric material]

[0043] In the resin composition of the low dielectric material used in the printed wiring board (2) using the low dielectric material as the insulating layer, the polyarylene sulfide resin (A) is used as the main component, and the thermoplastic resin (B) other than the polyarylene sulfide resin (A) having a glass transition temperature of 200° C. or above or a melting point of 230° C. or above is used as the raw material. At this time, the resin composition has a continuous phase and a dispersed phase, the continuous phase contains the polyarylene sulfide resin (A), and the dispersed phase contains the thermoplastic resin (B). In addition, the main component in the present invention means that when the resin composition as a whole is set to 100% by mass, the polyarylene sulfide resin accounts for more than 51% by mass. By including the thermoplastic resin (B) in the dispersed phase, the adhesion to the metal layer or the epoxy glass cloth laminate can be improved compared to using the PAS resin alone. In particular, the inclusion of the thermoplastic resin (B) which is an amorphous resin or a fluorine-based resin improves the unevenness followability or the flexibility is high, so that stress is less likely to be concentrated, thereby achieving a high effect of improving the adhesion to the metal layer or the epoxy glass cloth laminate.

[0044] The average dispersion diameter of the dispersed phase is 5 μm or less, preferably 3 μm or less, and more preferably 0.5 μm to 3 μm. If the average dispersion diameter of the dispersed phase is 5 μm or less, a uniform film can be obtained. In addition, in the present invention, the "average dispersion diameter of the dispersed phase" is set to a value measured by the method described in the Examples.

[0045] [Polyarylene sulfide resin (A)]

[0046] The polyarylene sulfide resin (A) is a main component of the resin composition and is a component having the function of imparting excellent heat resistance, chemical resistance, and dielectric properties to the insulating layer.

[0047] The PAS-based resin (A) is a polymer including a structure in which an aromatic ring and a sulfur atom are bonded to each other (specifically, a structure represented by the following formula (1)) as a repeating unit.

[0048] [Chemistry 1]

[0049]

[0050] (In the formula, R 1 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and n each independently represents an integer of 1 to 4)

[0051] Here, R in the structure represented by formula (1) 1 Preferably, all of them are hydrogen atoms. With such a structure, the mechanical strength of the PAS-based resin (A) can be further improved. 1 Examples of the structure represented by formula (1) in which all the atoms are hydrogen atoms include the structure represented by formula (2) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the para position) and the structure represented by formula (3) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the meta position).

[0052] [Chemistry 2]

[0053]

[0054] Among these, the structure represented by formula (1) is preferably the structure represented by formula (2). When the PAS-based resin (A) has the structure represented by formula (2), heat resistance and crystallinity can be further improved.

[0055] Furthermore, the PAS-based resin (A) may contain not only the structure represented by the above formula (1) but also the structures represented by the following formulae (4) to (7) as repeating units.

[0056] [Chemistry 3]

[0057]

[0058] Among all the repeating units constituting the PAS resin (A), the structures represented by formulae (4) to (7) are preferably included in an amount of 30 mol% or less, more preferably 10 mol% or less. Such structures can further improve the heat resistance or mechanical strength of the PAS resin (A).

[0059] The bonding form of the structures represented by formula (4) to formula (7) may be either random or block.

[0060] The PAS-based resin (A) may also contain a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like as a repeating unit in its molecular structure.

[0061] [Chemistry 4]

[0062]

[0063] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol% or less, and more preferably substantially not contained, among all repeating units constituting the PAS resin (A). Such a structure can reduce the chlorine atom content in the PAS resin (A).

[0064] In addition, as long as the effects of the present invention are not impaired, the properties of the PAS-based resin (A) are not particularly limited, but its melt viscosity (V6) at 300°C is preferably 100 Pa·s to 2000 Pa·s, and in terms of a better balance between fluidity and mechanical strength, it is more preferably 120 Pa·s to 1600 Pa·s.

[0065] Furthermore, the PAS resin (A) preferably has a peak in the molecular weight range of 25,000 to 40,000 in the measurement using gel permeation chromatography (GPC), and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is in the range of 5 to 10, and the non-Newtonian index is in the range of 0.9 to 1.3. By using the PAS resin (A), the content of chlorine atoms in the PAS resin (A) itself can be reduced to the range of 500 ppm to 2,000 ppm without reducing the mechanical strength of the film, and it is easy to apply to halogen-free electronic / electrical parts.

[0066] In addition, in this specification, the weight average molecular weight (Mw), the number average molecular weight (Mn) and the molecular weight distribution (Mw / Mn) are respectively the values ​​measured by gel permeation chromatography (GPC). In addition, the measurement conditions of GPC are as follows.

[0067] [Measurement conditions by gel permeation chromatography]

[0068] Device: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific)

[0069] Tube: UT-805L (manufactured by Showa Denko Co., Ltd.)

[0070] Column temperature: 210℃

[0071] Solvent: 1-Chloronaphthalene

[0072] Determination method: The molecular weight distribution and peak molecular weight were determined using an ultraviolet (UV) detector (360 nm) with six types of monodisperse polystyrenes used for calibration.

[0073] The method for producing the PAS-based resin (A) is not particularly limited, and examples thereof include: 1) a method in which a polyhalogenated aromatic compound or other copolymerization component is added to a dihalogenated aromatic compound in the presence of sulfur and sodium carbonate to polymerize the compound; 2) a method in which a polyhalogenated aromatic compound or other copolymerization component is added to a dihalogenated aromatic compound in the presence of a thioetherifying agent or the like in a polar solvent to polymerize the compound; 3) a method in which other copolymerization components are added to p-chlorothiophenol to self-condense the compound, etc. Among these production methods, the method 2) is generally used and is preferred.

[0074] Furthermore, during the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid or an alkali hydroxide may be added in order to adjust the degree of polymerization.

[0075] Among the above-mentioned methods 2), the following method 2-1) or method 2-2) is particularly preferred. In the method 2-1), a water-containing thioetherification agent is introduced into a mixture containing a heated organic polar solvent and a dihalogenated aromatic compound at a rate that can remove water from the reaction mixture, and when a polyhalogenated aromatic compound is added to the dihalogenated aromatic compound and the thioetherification agent in the organic polar solvent and reacted, the amount of water in the reaction system is controlled within a range of 0.02 mol to 0.5 mol relative to 1 mol of the organic polar solvent, thereby producing a PAS-based resin (A) (see Japanese Patent Laid-Open No. 07-228699).

[0076] In the method of 2-2), in the presence of a solid alkali metal sulfide and a non-protonic polar organic solvent, a polyhalogenated aromatic compound or other copolymer components are added to a dihalogenated aromatic compound as needed, and reacted with an alkali metal hydrosulfide and an organic acid alkali metal salt, the amount of the organic acid alkali metal salt is controlled within the range of 0.01 mol to 0.9 mol relative to 1 mol of the sulfur source, and the amount of water in the reaction system is controlled within the range of less than 0.02 mol relative to 1 mol of the non-protonic polar organic solvent, thereby producing a PAS-based resin (A) (refer to WO2010 / 058713 manual).

[0077] Specific examples of the dihalogenated aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and compounds wherein the aromatic ring of each of the above compounds has an alkyl group having 1 to 18 carbon atoms.

[0078] Examples of the polyhalogenated aromatic compound include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene.

[0079] Furthermore, the halogen atom contained in the above compound is preferably a chlorine atom or a bromine atom.

[0080] The reaction mixture containing the PAS-based resin (A) obtained in the polymerization step can be post-treated by a known and commonly used method. The post-treatment method is not particularly limited, and examples thereof include the following methods (1) to (5).

[0081] In the method (1), after the polymerization reaction is completed, the reaction mixture is first distilled under reduced pressure or normal pressure to remove the solvent directly or after adding an acid or a base. The solid matter after the solvent is distilled off is then washed once or twice with a solvent such as water, a reaction solvent (or an organic solvent having an equivalent degree of solubility for the low molecular weight polymer), acetone, methyl ethyl ketone, alcohol, etc., and then neutralized, washed with water, filtered and dried.

[0082] In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, aliphatic hydrocarbons, etc. (a solvent that is soluble in the polymerization solvent used and is at least a poor solvent for the PAS-based resin (A)) is added to the reaction mixture as a precipitant to precipitate solid products such as the PAS-based resin (A) and inorganic salts, which are then separated by filtration, washed, and dried.

[0083] In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then filtered to remove the low molecular weight polymer, and then washed once or twice with a solvent such as water, acetone, methyl ethyl ketone, alcohol, etc., and then neutralized, washed with water, filtered and dried.

[0084] In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture, the mixture is washed with water, filtered, and an acid is added during the washing with water, if necessary, for acid treatment, followed by drying.

[0085] In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or twice with a reaction solvent as necessary, and then washed with water, filtered, and dried.

[0086] Examples of the acid that can be used in the method (4) include saturated fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid, unsaturated fatty acids such as acrylic acid, crotonic acid, and oleic acid, aromatic carboxylic acids such as benzoic acid, phthalic acid, and salicylic acid, dicarboxylic acids such as maleic acid and fumaric acid, organic acids such as sulfonic acids such as methanesulfonic acid and p-toluenesulfonic acid, and inorganic acids such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid.

[0087] Examples of the hydrogen salt include sodium hydrogen sulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. Among them, when used in an actual device, an organic acid that has little corrosion on metal parts is preferred.

[0088] In the above methods (1) to (5), the drying of the PAS-based resin (A) may be performed in a vacuum, or in an atmosphere of an inert gas such as air or nitrogen.

[0089] In particular, the PAS resin (A) post-treated by the method of (4) can increase the amount of the acid group bonded to the end of its molecule, and when mixed with polyphenylene ether resin, fluorine resin, and modified elastomer (C), the effect of improving the dispersibility of these can be obtained. As an acid group, a carboxyl group is particularly preferred. If the content of the PAS resin (A) is within the range, the film can be given the original heat resistance and chemical resistance of the PAS resin, and the elongation can also be maintained. In addition, in the present invention, the main component refers to the total mass of the resin component used to form the resin composition, containing the specific resin at more than 50% by mass, and preferably containing more than 60% by mass.

[0090] In order to exhibit heat resistance, the PAS-based resin preferably has a melting point of not less than 275°C.

[0091] [Thermoplastic resin (B) other than polyarylene sulfide resin]

[0092] The thermoplastic resin (B) other than the polyarylene sulfide resin of the present invention (hereinafter sometimes referred to as "thermoplastic resin (B)") may be any thermoplastic resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher. For example, various polymers such as polyphenylene ether, polyether sulfone, polyphenyl sulfone, polyetherimide, polysulfone, fluorine-based resin, and blends containing at least one of these polymers can be used. Among them, polyphenylene ether or fluorine-based resin is preferred from the viewpoint of low dielectric properties, miscibility with PAS-based resin, adhesion to epoxy glass cloth substrate, and low hygroscopicity.

[0093] [Polyphenylene ether resin (PPE (polyphenylene ether) resin) (B1)]

[0094] Polyphenylene ether resin (PPE resin) is amorphous resin, therefore if more than the glass transition temperature, then soften below the melting point of PAS resin.Therefore, when following copper foil at a high temperature below the melting point of PAS resin or when annealing, the PAS resin as a crystalline polymer is separately, and the resin composition dispersed with the PPE resin as amorphous resin improves the follow-up to the concavoconvexity of copper foil, and can improve the close adhesion strength of resin and copper foil.In addition, PPE resin is owing to having the feature of low dielectric loss tangent, therefore also has following feature: for the polymer of dielectric loss tangent difference such as polycarbonate, it is easier to obtain the physical property suitable for high frequency use.In addition, PPE resin has aromatic ring or oxygen-containing functional group, therefore also has the feature that close adhesion is more excellent than aliphatic hydrocarbon such as polypropylene (PP).

[0095] The PPE-based resin is a homopolymer and / or copolymer having a structural part represented by the following structural formula (9).

[0096] [Chemistry 5]

[0097]

[0098] In the formula, R2 is independently a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbon group, or a halogenated hydrocarbon group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and m is independently an integer of 1 to 4.

[0099] Specific examples of PPE-based resins include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), and further polyphenylene ether copolymers such as copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol or 2-methyl-6-butylphenol). Among them, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is further preferred.

[0100] The content of the PPE-based resin is preferably 3% to 49% by mass relative to the total amount of organic components in the resin composition, more preferably 5% to 40% by mass from the viewpoint of uniform dispersion in the composition, and further preferably 10% to 35% by mass for further uniform dispersion.

[0101] The number average molecular weight of the PPE-based resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and still more preferably 500 to 30,000.

[0102] [Fluorine-based resin (B2)]

[0103] Fluorine resin has the characteristics of low dielectric loss tangent or low water absorption, etc., which are suitable for high-frequency insulating substrates. Furthermore, when dispersed in PAS resin, through its flexibility, the effect of improving the follow-up of PAS resin to the concavoconvex of metal layer or epoxy glass cloth laminate can be exerted, and the close contact strength can be improved. The structure of fluorine resin (B2) is not particularly limited, and comprises at least one fluoroolefin unit. For example, it can also be listed: tetrafluoroethylene polymer or copolymers with perfluoro (alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, fluorinated vinyl, trifluoroethylene, chlorotrifluoroethylene, and copolymers with non-fluorine vinyl monomers such as ethylene, propylene, butene, alkyl vinyl ethers, etc. that do not contain fluorine. Specifically, it can be listed: polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro (alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. Among them, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer are preferred in terms of easy melt extrudability.

[0104] Among the fluorine-based resins (B2), fluorine-based resins (B2) having functional groups are also preferred. As fluorine-based resins (B2) having functional groups, at least one reactive functional group selected from the group consisting of a carbonyl-containing group, a hydroxyl group, an epoxy group, and an isocyanate group is present. These reactive functional groups may also include two or more. Among them, in terms of excellent reactivity with the PAS-based resin (A), a carbonyl-containing group is preferred. As the carbonyl-containing group, groups having a carbonyl group between carbon atoms of a hydrocarbon group, carbonate groups, carboxyl groups, haloformyl groups, alkoxycarbonyl groups, anhydride groups, polyfluoroalkoxycarbonyl groups, etc. can be cited.

[0105] As a method for introducing reactive functional groups into a fluororesin (B2) having functional groups, (1) when manufacturing the main chain of the fluororesin having functional groups by polymerization reaction, a monomer having reactive functional groups is used. (2) A chain transfer agent that generates free radicals having reactive functional groups is used to manufacture the fluororesin (B2) having functional groups by polymerization reaction. (3) A polymerization initiator that generates free radicals having reactive functional groups is used to manufacture the fluororesin (B2) having functional groups by polymerization reaction. Examples include (4) a method of modifying the fluororesin by oxidation, thermal decomposition, etc. Examples include (5) a method of preparing a compound or resin that is compatible with the fluororesin and contains the functional groups.

[0106] Examples of the reactive functional group-containing monomer include a monomer having a carbonyl group-containing group, an epoxy group-containing monomer, a hydroxyl group-containing monomer, and an isocyanate group-containing monomer.

[0107] Examples of the monomer having a carbonyl-containing group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, bicycloheptenedicarboxylic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid), unsaturated dicarboxylic anhydrides thereof, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butyrate, vinyl trimethylacetate, vinyl benzoate, vinyl crotonate), and the like.

[0108] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing vinyl esters, hydroxyl group-containing vinyl ethers, hydroxyl group-containing allyl ethers, hydroxyl group-containing (meth)acrylates, hydroxyethyl crotonate, and allyl alcohol.

[0109] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).

[0110] As the isocyanate group-containing monomer, 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate, etc. can be mentioned.

[0111] The amount of reactive functional groups contained in the fluororesin (B2) having a functional group is preferably 0.01 mol% to 3 mol%, more preferably 0.03 mol% to 2 mol%, and further preferably 0.05 mol% to 1 mol% in all units constituting the fluororesin (B2) having a functional group. If the amount of reactive functional groups is within the above range, the reactivity with the PAS-based resin is excellent and deterioration of fluidity can be suppressed.

[0112] The melting point of the fluororesin (B2) used in the present invention is not particularly limited, but is 230 to 320° C., preferably 250 to 310° C., and more preferably 260 to 300° C. When the melting point of the fluororesin (B2) is within the above range, heat resistance can be maintained and good melt extrusion stability can be obtained.

[0113] The glass transition temperature of the fluorine resin (B2) used in the present invention is not particularly limited, but is 110°C or less, more preferably 100°C or less. If the fluorine resin (B2) has the glass transition temperature, the dispersed phase of the fluorine resin (B2) is also extended at the extension temperature of the PAS resin (A) during the extension after mixing with the PAS resin (A), so that the peeling at the interface between the PAS resin (A) as the continuous phase and the fluorine resin (B2) as the dispersed phase can be suppressed. Thus, the fracture during the extension can be suppressed, and a film with excellent mechanical properties can be obtained.

[0114] Relative to the total amount of organic components in the resin composition, the content of the fluorine-based resin (B2) in the resin composition is preferably 3% to 49% by mass, and from the perspective of uniform dispersion in the composition, it is more preferably 5% to 40% by mass, and in order to further uniformly disperse, it is further preferably 10% to 35% by mass. If the content of the fluorine-based resin (B2) is within the range, the dielectric properties of the film (low dielectric constant) can be more significantly improved.

[0115] In the present invention, a fluorine-based resin (B2) can also be used in combination with the PPE-based resin (B1).

[0116] [Modified elastomer (C)]

[0117] The modified elastomer (C) is a component having the function of improving the mechanical strength (folding strength, etc.) of the insulating layer by having a reactive group that can react with at least one of the PAS-based resin (A), the PPE-based resin (B1), and the fluorine-based resin (B2).

[0118] The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of epoxy groups and acid anhydride groups, and more preferably epoxy groups. These reactive groups can react rapidly with the functional groups at the molecular terminals of the PAS resin (A), the PPE resin (B1), and the fluorine resin (B2).

[0119] Examples of the modified elastomer (C) include copolymers comprising repeating units based on α-olefins and repeating units based on a vinyl polymerizable compound having the functional group, copolymers comprising repeating units based on α-olefins, repeating units based on a vinyl polymerizable compound having the functional group, and repeating units based on acrylates, and the like.

[0120] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1.

[0121] Examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; maleic acid, fumaric acid, itaconic acid; other unsaturated dicarboxylic acids having 4 to 10 carbon atoms; their monoesters or diesters; and their anhydrides; α,β-unsaturated dicarboxylic acids; their esters and their anhydrides; and α,β-unsaturated glycidyl esters.

[0122] The α,β-unsaturated glycidyl ester is not particularly limited, and examples thereof include compounds represented by the following formula (10).

[0123] [Chemistry 6]

[0124]

[0125] In the formula, R 3 It is an alkenyl group having 1 to 6 carbon atoms.

[0126] Examples of the alkenyl group having 1 to 6 carbon atoms include ethenyl, 1-propenyl, 2-propenyl, 1-methylethenyl, 1-butenyl, 2-butenyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-methyl-1-pentenyl, 1-methyl-3-pentenyl, 1,1-dimethyl-1-butenyl, 1-hexenyl, and 3-hexenyl.

[0127] R 4 Each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.

[0128] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

[0129] Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, 2-methylbutyl, 3-methylbutyl, 2,2-dimethylpropyl, hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,4-dimethylbutyl, 3,3-dimethylbutyl, and 2-ethylbutyl.

[0130] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, and glycidyl methacrylate is preferred.

[0131] The ratio of the repeating unit based on α-olefin in the modified elastomer (C) is preferably 50% to 95% by mass, more preferably 50% to 80% by mass. If the ratio of the repeating unit based on α-olefin is within the above range, the stretching uniformity and folding strength of the film can be improved.

[0132] In addition, the ratio of the repeating unit based on the vinyl polymerizable compound having a functional group in the modified elastomer (C) is preferably 1% to 30% by mass, and more preferably 2% to 20% by mass. If the ratio of the repeating unit based on the vinyl polymerizable compound having a functional group is within the above range, not only the target improvement effect can be obtained, but also good extrusion stability can be obtained.

[0133] The content of the modified elastomer (C) in the resin composition is preferably 1 to 15% by mass, more preferably 3 to 10% by mass. When the content of the modified elastomer (C) is within the above range, the effect of improving the folding strength etc. can be significantly exerted.

[0134] [Silane coupling agent]

[0135] In the present invention, a silane coupling agent is preferably used as a component having a function of improving the affinity (interaction) between the PAS-based resin (A) and other components (PPE-based resin (B1), fluorine-based resin (B2), and modified elastomer (C)), so that the dispersibility of other components in the PAS-based resin (A) is greatly improved, and a good morphology can be formed.

[0136] The silane coupling agent is preferably a compound having a functional group that can react with a carboxyl group. The silane coupling agent reacts with any one of the PAS resin (A), the PPE resin (B1), the fluorine resin (B2), and the modified elastomer (C) to form a strong bond with them. As a result, the effect of the silane coupling agent can be more significantly exerted, and the dispersibility of the PPE resin (B1), the fluorine resin (B2), and the modified elastomer (C) in the PAS resin (A) can be particularly improved.

[0137] Examples of the silane coupling agent include compounds having an epoxy group, an isocyanate group, and an amino group.

[0138] Specific examples of the silane coupling agent include epoxy group-containing alkoxysilane compounds such as γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyl Alkoxysilane compounds containing isocyanate groups such as dimethoxysilane, γ-isocyanatepropylethyldiethoxysilane, and γ-isocyanatepropyltrichlorosilane, alkoxysilane compounds containing amino groups such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane, and alkoxysilane compounds containing hydroxy groups such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.

[0139] The content of the silane coupling agent in the resin composition is preferably 0.1% to 5% by mass, more preferably 0.2% to 2.5% by mass. When the content of the silane coupling agent is within the above range, the dispersibility of other components in the PAS-based resin (A) can be significantly improved.

[0140] [additive]

[0141] The resin composition may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a UV stabilizer, a lubricant, an antistatic agent, and a colorant within a range that does not inhibit the effects of the present invention.

[0142] [Low dielectric material (resin composition and film)]

[0143] <Method for producing resin composition>

[0144] The method for producing the resin composition is not particularly limited, and the following method can be cited, that is, a method of uniformly mixing the PAS resin (A), the thermoplastic resin (B), and other components (modified elastomer (C), silane coupling agent) as required by a drum mixer or a Henschel mixer, and then feeding the mixture into a twin-screw extruder for melt kneading, wherein the melt kneading may be either or both of kneading in a shear flow field and kneading in an elongation flow field. The melt kneading is preferably carried out under the condition that the ratio of the ejection amount (kg / hr) of the kneaded material to the screw speed (rpm) (ejection amount / screw speed) is 0.02 (kg / hr·rpm) to 0.2 (kg / hr·rpm).

[0145] The setting temperature during mixing can be selected from the range of the melting point of the resin with a higher melting point among the PAS resin (A) and the thermoplastic resin (B) + 5°C to 70°C, and more preferably from the range of +10°C to 50°C. When the setting temperature is lower than the melting point of the PAS resin (A) and the thermoplastic resin (B), the viscosity of the composition increases significantly due to the presence of partially unmelted PAS resin (A) or thermoplastic resin (B), and the load on the twin-screw extruder increases, which is not preferred in terms of productivity.

[0146] If described in more detail, the following method is preferred: each component is put into a twin-screw extruder, and melt-kneading is performed under the temperature conditions of the set temperature and the resin temperature in the strand die of about 310°C. At this time, the ejection amount of the mixed material is in the range of 5kg / hr to 50kg / hr at a rotation speed of 250rpm. In particular, from the perspective of improving the dispersibility of each component, the ejection amount of the mixed material is preferably 20kg / hr to 35kg / hr at a rotation speed of 250rpm. Therefore, the ratio of the ejection amount (kg / hr) of the mixed material to the screw speed (rpm) (ejection amount / screw speed) is more preferably 0.08 (kg / hr·rpm) to 0.14 (kg / hr·rpm).

[0147] <Film>

[0148] The insulating layer of the printed wiring board (2) of the present invention can be formed by the PAS-based film produced from the above-described resin composition.

[0149] In one embodiment of the PAS-based film, the PAS-based resin (A) serves as a matrix (continuous phase), and particles (dispersed phase) containing a PPE-based resin (B1) and a fluorine-based resin (B2) are dispersed in the matrix.

[0150] In addition, the present inventors believe that the modified elastomer (C) also functions as a compatibilizer for the PAS-based resin (A) and the PPE-based resin (B1) and the fluorine-based resin (B2), thereby finely dispersing the particles in the matrix, thereby improving the mechanical strength of the film. Furthermore, the present inventors believe that by using the modified elastomer (C) in combination with a silane coupling agent, the adhesion at the interface between the matrix and the particles is further improved, and the mechanical strength of the film is further improved.

[0151] The film is preferably a biaxially stretched film obtained by biaxially stretching a sheet obtained from a resin composition. If a biaxially stretched film is made, the PAS-based resin (A) constituting the matrix is ​​crystallized in a state where its molecular chain is stretched, so a film with high dimensional accuracy can be obtained. However, in the case of needing to reduce costs, a non-stretched film with fewer steps can also be selected.

[0152] The stretching ratio in the longitudinal direction (machine direction (MD)) of the biaxially stretched film is preferably 1.5 to 4 times, more preferably 2.0 to 3.8 times.

[0153] The stretching ratio in the width direction (transverse direction (TD)) of the biaxially stretched film is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times.

[0154] In addition, the ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the long side direction (MD direction) of the biaxially stretched film (width direction (TD direction) / long side direction (MD direction)) is preferably 0.8 to 1.3, and in terms of balancing the physical properties in the long side direction and the physical properties in the width direction, it is more preferably 0.9 to 1.2.

[0155] <Method for producing biaxially stretched film>

[0156] The biaxially stretched film is produced, for example, as follows.

[0157] First, the resin composition is dried at 140°C for 3 hours or more, and then introduced into an extruder heated at 280°C to 320°C.

[0158] Thereafter, the molten resin composition (ie, kneaded product) that has passed through the extruder is ejected into a sheet (film) form using a T-die.

[0159] Next, the sheet-shaped kneaded product is brought into close contact with a cooling roll having a surface temperature of 20° C. to 50° C. to be cooled and solidified. Thus, an unoriented, unstretched sheet is obtained.

[0160] Next, the unstretched sheet is subjected to biaxial stretching. As the stretching method, a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a method combining these methods can be used.

[0161] When biaxial stretching is performed using a sequential biaxial stretching method, the unstretched sheet is heated, for example, using a heating roller group, and stretched in the long side direction (MD direction) by 1.5 to 4 times (preferably 2.0 to 3.8 times) and in one stage or more than two stages, and then cooled using a cooling roller group at 30°C to 60°C.

[0162] The stretching temperature is preferably the glass transition temperature (Tg) of the PAS-based resin (A) to Tg+40°C, more preferably Tg+5°C to Tg+30°C, and still more preferably Tg+5°C to Tg+20°C.

[0163] Next, the film is stretched in the width direction (TD direction) by using a tenter. Both ends of the film stretched in the MD direction are gripped with clips and guided to the tenter to be stretched in the TD direction.

[0164] Furthermore, the stretching ratio is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times.

[0165] The stretching temperature is preferably Tg to Tg+40°C, more preferably Tg+5°C to Tg+30°C, and still more preferably Tg+5°C to Tg+20°C.

[0166] Next, the stretched film is heat-fixed while being stretched or relaxed in the width direction.

[0167] The heat setting temperature is not particularly limited, but is preferably 200°C to 280°C, more preferably 220°C to 280°C, and further preferably 240°C to 275°C. In addition, the heat setting may be performed in two stages by changing the heat setting temperature. In the above case, it is preferred that the heat setting temperature of the second stage is higher by +10°C to 40°C than the heat setting temperature of the first stage. The heat resistance and mechanical strength of the stretched film heat-set at the heat setting temperature within the above range are further improved.

[0168] In addition, the heat setting time is preferably 1 second to 60 seconds.

[0169] Furthermore, the film is cooled while being relaxed in the width direction in a temperature range of 50° C. to 270° C. The relaxation rate is preferably 0.5% to 10%, more preferably 2% to 8%, and even more preferably 3% to 7%.

[0170] In order to improve the thermal stability of the film, heat treatment (annealing treatment) may also be further performed. As a heat treatment method after stretching, for example, known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves can be cited. Among them, the method of blowing hot air is preferred in terms of uniform and high-precision heating. The heat treatment temperature is preferably set to 150°C to 260°C, and more preferably to 160°C to 240°C. If the heat treatment is not performed, it is difficult to relax the stress of the film. In addition, if the heat treatment is performed at a temperature below 150°C, sufficient stress relaxation cannot be performed, and the thermal shrinkage of the film after production cannot be reduced. As a result, it is difficult to achieve the thermal stability of the film. In addition, if the heat treatment temperature is above 260°C, a portion of the crystalline phase of polyphenylene sulfide is melted, and the orientation is destroyed. Therefore, the linear expansion coefficient in the plane direction of the film after production deteriorates. As a result, it is difficult to achieve the thermal stability of the film. The heat treatment time is preferably set to 3 seconds to 300 seconds, and more preferably to 5 seconds to 100 seconds.

[0171] [Hybrid substrate for high frequency]

[0172] The high-frequency hybrid substrate of the present invention can be manufactured by laminating a printed wiring board (2) having a PAS film as an insulating layer on a printed wiring board (1) including an insulating layer formed by an epoxy glass cloth laminate. Alternatively, it can be manufactured by laminating a copper-clad PAS film on the printed wiring board (1) and then forming wiring on the outermost copper layer using a known method. Alternatively, it can be manufactured by laminating a PAS film and a metal layer on the printed wiring board (1) in sequence or simultaneously and forming wiring on the outermost layer using a known method. The attachment of the above-mentioned materials to the printed wiring board (1) can be selected by a known method. For example, it can be manufactured by direct lamination based on hot pressing utilizing the thermoplasticity of the PAS film, or by lamination using an adhesive, a bonding sheet or a prepreg. Furthermore, a printed circuit board can be obtained by connecting electronic components and operating as an electronic circuit.

[0173] [Millimeter wave radar, antenna]

[0174] The high-frequency hybrid substrate of the present invention is most suitable as a substrate for millimeter-wave radars and antennas used in high frequencies. As a vehicle-mounted millimeter-wave radar or an antenna for 5G smartphones, it has the advantage of low transmission loss and can accelerate miniaturization or communication speed.

[0175] [Example]

[0176] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these.

[0177] [Example 1]

[0178] A mixture was obtained by uniformly mixing 80 parts by mass of a PAS resin (A) (linear polyphenylene sulfide, manufactured by DIC Corporation) and 20 parts by mass of a polyphenylene ether resin (PPE resin) (B1), namely PX-100 (manufactured by Mitsubishi Engineering Plastics Co., Ltd.) using a tumble mixer.

[0179] Then, the obtained mixture was put into a twin-screw extruder "TEX-30α" with a vent manufactured by The Japan Steel Works, Ltd. The mixture was melt-extruded under the conditions of a discharge rate of 20 kg / hr, a screw speed of 300 rpm, and a set temperature of 300° C. and discharged in a wire-like state, and then cooled with water at a temperature of 30° C. and cut to produce a resin composition.

[0180] The average particle size of particles in the produced resin composition was measured as follows.

[0181] First, the resin composition particles were cut in a direction perpendicular to the flow direction using an ultrathin sectioning method. Next, a scanning electron microscope (SEM) photograph was taken at 2000 times for each cut surface of the cut particles, and the obtained image was enlarged to A3 size. Next, 50 particles were selected from the enlarged SEM photograph, and the maximum diameter of each particle in the cut surface was measured to calculate the average particle size.

[0182] As a result, the average particle size of particles in the resin composition pellets was 0.9 μm.

[0183] In addition, the resin particles containing the resin composition obtained in the above were subjected to SEM-energy disperse spectroscopy (EDS) analysis to analyze the components of the matrix and particles constituting the resin composition particles. The results showed that the component constituting the matrix was a PAS-based resin, and the component constituting the particles was a PPE resin.

[0184] Next, the resin composition was dried at 140° C. for 3 hours and then put into a single-screw extruder with a full-flighted screw to be melted at 280° C. to 310° C. The molten resin composition was extruded from a T-die and then closely cooled using a chill roll set at 40° C. to prepare an unstretched sheet.

[0185] Next, the unstretched sheet was biaxially stretched to 3.0×3.0 times at 100° C. using a batch biaxial stretching machine (manufactured by Imoto Manufacturing Co., Ltd.) to obtain a film with a thickness of 50 μm. The obtained film was then fixed to a mold frame and heat-set in an oven at 275° C. to produce a biaxially stretched film.

[0186] A 12 μm thick copper layer was formed on the obtained biaxially stretched film by double-sided sputtering to obtain a copper-clad laminate. Furthermore, a wiring pattern was formed on the copper layer by resist etching to obtain a printed wiring board (2).

[0187] Next, a wiring pattern was made on an epoxy glass cloth laminate (manufactured by Sunhayato, substrate thickness 1.6 mm, copper foil thickness 18 μm) with copper foil attached to both sides by a resist etching method to obtain a printed wiring board (1). The printed wiring board (1), glass cloth substrate / epoxy resin prepreg (manufactured by Lichang Industrial Co., Ltd., substrate thickness 0.18 mm), and the printed wiring board (2) were stacked in this order and heated by vacuum pressing to manufacture a high-frequency hybrid substrate. In addition, the prepreg has the effect of bonding the upper surface and the lower surface by heat treatment, and becomes an epoxy glass cloth layer after hardening.

[0188] [Example 2]

[0189] A high-frequency hybrid substrate is manufactured in the same manner as in Example 1 except that a printed wiring board (2) is used as an insulating layer using a resin composition comprising 80 parts by mass of a PAS-based resin (A), 10 parts by mass of PX-100 (B1), and 10 parts by mass of a fluorine-based resin, namely EA-2000 (manufactured by AGC Co., Ltd., melting point 300°C) (B2). The printed wiring board (2) is laminated on both surfaces of the printed wiring board (1) via a glass cloth substrate / epoxy resin prepreg.

[0190] [Example 3]

[0191] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that the PAS-based resin (A) was 70 parts by mass, the PX-100 (B1) was 20 parts by mass, and the EA-2000 (B2) was 10 parts by mass.

[0192] [Example 4]

[0193] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that 60 parts by mass of PAS-based resin (A), 10 parts by mass of PX-100 (B1) and 30 parts by mass of EA-2000 (B2) were used and a high-frequency single-sided copper-clad laminate and a printed wiring board (1) were laminated using a bonding sheet.

[0194] [Example 5]

[0195] A high-frequency hybrid substrate is manufactured in the same manner as in Example 1 except that 67 parts by mass of PAS-based resin (A), 20 parts by mass of PX-100 (B1), 10 parts by mass of EA-2000 (B2), and 3% by mass of modified elastomer (C), namely Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate = 70 / 3 / 27 (mass %), sometimes referred to as "BF7L" hereinafter).

[0196] [Example 6]

[0197] A high frequency hybrid substrate was produced in the same manner as in Example 1 except that 80 parts by mass of the PAS resin (A), 20 parts by mass of PX-100 (manufactured by Mitsubishi Engineering-Plastics Co., Ltd.), and 0.3 parts by mass of a silane coupling agent were uniformly mixed using a tumble mixer.

[0198] [Example 7]

[0199] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that a polyphenylsulfone resin (B3) (manufactured by BASF, glass transition temperature 220° C., hereinafter sometimes referred to as “PPSU”) was used as the thermoplastic resin (B).

[0200] [Example 8]

[0201] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that a polysulfone resin (B4) (manufactured by Solvay Co., Ltd., glass transition temperature 190° C., hereinafter sometimes referred to as “PSU”) was used as the thermoplastic resin (B).

[0202] (Comparative Example 1)

[0203] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that the amount of the PAS-based resin (A) was 50 parts by mass and the amount of PX-100 (B1) was 50 parts by mass.

[0204] (Comparative Example 2)

[0205] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that 100 parts by mass of the PAS-based resin (A) and PX-100 were not used.

[0206] (Comparative Example 3)

[0207] A high-frequency hybrid substrate was produced in the same manner as in Example 1 except that the PAS-based film was replaced with a film of 100 parts by mass of a standard polyimide (manufactured by Toray DuPont, with a thickness of 50 μm).

[0208] 2. Evaluation

[0209] 2-1. Extension

[0210] Thirty unstretched sheets were biaxially stretched using a PAS-based resin to evaluate the success rate of obtaining stretched films without breaking.

[0211] [Evaluation criteria]

[0212] ◎:More than 90%

[0213] ○:More than 70%

[0214] ×: Less than 70%

[0215] 2-2. Dielectric constant and dielectric loss tangent

[0216] The dielectric constant is evaluated based on the cavity resonance method specified in Japanese Industrial Standards (JIS) C 2565: 1992. Specifically, a strip of 2 mm wide × 150 mm long is made from a PAS film or a polyimide film. Then, the produced strip is left to stand for 24 hours in an environment of 23°C and 50% Rh, and then the dielectric constant at a frequency of 1 GHz is measured using the cavity resonance method using the ADMS010c series (manufactured by Altai (aet) Co., Ltd.). When the dielectric constant is less than 3.2, it is set to ◎, if it is less than 3.4, it is set to ○, and if the dielectric constant is greater than 3.4, it is set to ×. A dielectric loss tangent of 0.003 or less is set to ◎, a dielectric loss tangent of 0.004 or less is set to ○, and above it is set to ×.

[0217] 2-3. Metal Adhesion

[0218] Regarding metal adhesion, the peel strength between the metal layer and the PAS-based film or the polyimide film was measured based on the test method specified in JIS K 6854:1999, and evaluated according to the following criteria.

[0219] ◎: 5N / cm or more

[0220] ○: 4N / cm or more and less than 5N / cm

[0221] ×: less than 4N / cm

[0222] 2-4. Flame retardancy

[0223] Based on the standard of UL94 VTM-0 (vertical burning test for plastic thin materials), 5 test pieces of 200mm×50mm are used to evaluate flame retardancy. If the flame retardancy is VTM-0, it is set as ○, and other than that, it is set as ×. Here, VTM-0 sets the following conditions as conditions, that is, the burning time after the first flame contact of each sample (hereinafter referred to as t1) and the burning time after the second flame contact (hereinafter referred to as t2) are both less than 10 seconds, and the t1+t2 of the 5 samples are all less than 50 seconds, and the total of t2 of each sample after the second flame contact and the remaining time (the time when it burns red without emitting flames) is less than 30 seconds, and there is no residual flame or dust until the retaining clip of each sample, and there is no ignition of the marking cotton caused by the flaming substance or the dripping object.

[0224] 2-5. Adhesion to the insulating layer formed by epoxy glass cloth laminate

[0225] Regarding the adhesion of the epoxy glass cloth, the epoxy glass cloth laminate and the PAS-based film were bonded together by hot pressing using a prepreg at 150° C. for 1 hour, and then the peel strength was measured and evaluated based on the following criteria.

[0226] ◎: 5N / cm or more

[0227] ○: 4N / cm or more and less than 5N / cm

[0228] ×: less than 4N / cm

[0229] 2-6. Low warpage

[0230] When a high-frequency hybrid substrate with a size of 10 cm square was formed, a case where the warpage at all four corners was less than 1.0 mm was rated as ○, and the cases other than that were rated as ×.

[0231] 2-7. Transmission loss

[0232] Microstrip lines were manufactured using a high-frequency hybrid substrate, and the transmission loss at 50 GHz was evaluated by a network analyzer (manufactured by Keysight Technologies) using a probe method. Less than -8.0 dB / 100 mm was marked as ◎, less than -9.0 dB / 100 mm was marked as ○, and greater than this was marked as ×.

[0233] 2-8. Reflow resistance

[0234] The obtained high-frequency hybrid substrate was heat treated at 260° C. for 30 minutes in a hot air dryer. The case where the PAS film did not deform or peel off, such as undulation or expansion, was rated as ○, and the case where the PAS film deformed, such as undulation or expansion, was rated as ×.

[0235] The above results are summarized in Tables 1 to 3.

[0236] [Table 1]

[0237]

[0238] *PAS; polyarylene sulfide resin PPE; polyphenylene ether resin PPSU; polyphenylene sulfone resin PSU; polysulfone resin [Table 2]

[0239]

[0240] [Table 3]

[0241]

Claims

1. A high frequency hybrid substrate, wherein a printed wiring board (2) having a low dielectric material as an insulating layer is laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate, wherein the high frequency hybrid substrate is characterized in that: The low dielectric material includes a resin composition of a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher.

2. The high-frequency hybrid substrate according to claim 1, wherein the ratio of the blending amount of the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher relative to the total amount of 100% by mass of the polyarylene sulfide resin (A) and the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is in the range of 3% by mass to 49% by mass. 3 . The high-frequency hybrid substrate according to claim 1 , wherein the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is a dispersed phase having an average dispersed diameter of 5 μm or less.

4. The high-frequency hybrid substrate according to claim 1 or 2, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is at least one selected from the group consisting of polyphenylene ether resin, polyether sulfone resin, polyphenylene sulfone resin, polyetherimide resin, polysulfone resin, and fluorine-based resin. 5 . The high-frequency hybrid substrate according to claim 1 , wherein the low-dielectric material has a dielectric constant of 3.4 or less.

6. The high-frequency hybrid substrate according to claim 1 or 2, further comprising a modified elastomer (C) which imparts a reactive group to the resin composition of the low dielectric material.

7. The high-frequency hybrid substrate according to claim 6, wherein the modified elastomer (C) comprises an olefin polymer having at least a functional group selected from an epoxy group and an acid anhydride group.

8. The high-frequency hybrid substrate according to claim 6, wherein the modified elastomer (C) is blended in an amount of 1 to 15% by mass relative to 100% by mass of the total of the polyarylene sulfide resin (A), the thermoplastic resin (B), and the modified elastomer (C). 9 . The high-frequency hybrid substrate according to claim 6 , wherein the α-olefin content of the modified elastomer (C) is 50% by mass to 95% by mass based on the total mass of the modified elastomer.

10. The high-frequency hybrid substrate according to claim 6, further comprising 0.01% by mass to 5% by mass of a silane coupling agent (D) having at least one functional group selected from an epoxy group, an amino group, and an isocyanate group.

11. A millimeter wave radar, comprising the high frequency hybrid substrate according to claim 1 or 2.

12. An antenna comprising the high frequency hybrid substrate according to claim 1 or 2.

Citation Information

Patent Citations

  • Packed tapes ae well as methods and assembly for packing said tapes

    EA002000B1

  • Multilayered printed wiring board

    JP1994005998A

  • Production of polyarylene sulfide polymer

    JP1995228699A

  • Multilayer printed wiring board

    JP2016040797A

  • Multilayer circuit board

    JP2020174115A